A Mathematical Model to Assess the Effect of Residual Positive Lymph Nodes on the Survival of Patients With Papillary Thyroid Microcarcinoma - Liu, Wen; Yan, Xuejing; Dong, Zhizhong; Su, Yanjun; Ma, Yunhai; Zhang, Jianming; Diao, Chang; Qian, Jun; Ran, Tao; Cheng, Ruochuan (Frontiers in Oncology, 2022)
Background: Active surveillance (AS) has been considered as the first-line management for patients with clinical low-risk papillary thyroid microcarcinoma (PTMC), who often have had lymph node micro-metastasis (m-LNM) when diagnosed. The paradox of “low-risk” and “high prevalence of m-LNM” is a potential barrier to acceptance of active surveillance (AS) for thyroid cancer both in surgeons and patients. Methods: Patients diagnosed with PTMC who underwent thyroidectomy with at least one LN examined were identified from a tertiary center database (n= 5,399). A β-binomial distribution was used to estimate the probability of missing nodal disease as a function of the number of LNs examined. Overall survival (OS) probabilities of groups with adequacy and inadequacy LNs examined were estimated using the Kaplan-Meier method in the Surveillance, Epidemiology, and End Results (SEER) database (n= 15,340). A multivariable model with restricted cubic splines was also used to verify the association of OS with the numbers of LN examined. Results: The risk of m-LNM residual in body (missed nodal disease) is from 31.3% to 10.0% if LNs examined number between 1 and 7 in patients with PTMC. with 7 LNs examined as the cut-off value, the intergroup comparison showed residual positive LNs did not affect OS both across all patients and aged ≥ 55 group (P=0.72 and P=0.112). After adjusting of patients and clinical characteristics, the multivariate model was also showed the slight effect between LN examined numbers and OS. (P=0.69) Conclusion: Even with the high prevalence, OS is not significantly compromised by persistent m-LNM in body in patients with low-risk PTMC. These findings suggest that the concerns of LNM should not be viewed as obstacle to developing AS in thyroid cancer. For patients with surgery, prophylactic LND does also not bring survival benefit in PTMC.